Respuesta :
5w + 9z = 2z + 3w
5w = -7z + 3w
2w = -7z
w = -7/2 z
The answer is A. w = -7/2 z
5w = -7z + 3w
2w = -7z
w = -7/2 z
The answer is A. w = -7/2 z
Answer: The correct option is
(A) [tex]w=-\dfrac{7}{2}z.[/tex]
Step-by-step explanation: We are given to solve the following equation for w :
[tex]5w+9z=2z+3w~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To solve the given equation for w, we must find the expression for w in terms of z.
From equation (i), we have
[tex]5w+9z=2z+3w\\\\\Rightarrow 5w-3w=2z-9z\\\\\Rightarrow 2w=-7z\\\\\Rightarrow w=-\dfrac{7}{2}z.[/tex]
Thus, the required solution for w is [tex]w=-\dfrac{7}{2}z.[/tex]
Option (A) is CORRECT.